The Effect of Interactional Teaching Style on Student Learning Outcomes on Respiratory System Material - Dina Oktaviani; Mufti Ali; Romy Faisal Mustofa (Bioedukasi: Jurnal Pendidikan Biologi, 2024)
An interactional teaching style is needed for the learning process in the classroom. The use of an interactional teaching style is believed to affect student learning outcomes. This study aims to determine the interactional teaching style on student learning outcomes in the material on the respiratory system in class XI MIPA SMA Negeri 2 Singaparna Academic Year 2022/2023. The research method uses a quasi-experiment with a research design called a nonequivalent pretest-posttest control group design. The population in this study were all class XI MIPA SMA Negeri 2 Singaparna with 4 classes totaling 215 students. The sample technique used was purposive sampling with the sample used being class XI MIPA 2 as the experimental class and class XI MIPA 4 as the control class with 60 students. The instrument used in this study was to measure student learning outcomes referring to the taxonomic bloom indicators of indicators C1, C2, C3, C4, and C5. The data analysis technique used is the independent t-test. The results of the study show that there is a significant effect of using an interactional teaching style on student learning outcomes with a significance value of 0.000 <0.05. It can be concluded that there is an influence of interactional teaching style on the learning outcomes of students in class XI MIPA SMAN 2 Singaparna Academic Year 2022/2023 on the material of the respiratory system.